Structural, magnetic, and optical characteristics of undoped and chromium, iron, cobalt, copper, and zinc doped nickel oxide nanopowders - Farzaneh Asaldoust; Khosro Mabhouti; Akbar Jafari; Maryam Taleb-Abbasi (Scientific Reports)
Abstract The present investigation seeks to customize the optical, magnetic, and structural characteristics of nickel oxide (NiO) nanopowders through chromium, iron, cobalt, copper, and zinc doping to enhance optoelectronic applications. In this regard, the preparation of pristine NiO and Ni0.95 × 0.05O (X = Cr, Fe, Co, Cu, and Zn) powders was successfully achieved through the co-precipitation method. The X-ray powder diffraction was employed to examine the prepared powders’ phase formation and crystal structure characteristics. The obtained results revealed the presence of a face-centered cubic structure in all samples. In addition, doping of Cr, Fe, Co, Cu, and Zn into the NiO system did not induce any other secondary phase. Moreover, the estimation of the crystalline size for the pristine and doped samples was carried out using the Debye-Scherrer formula, yielding values ranging from 16 to 28 nm which is deemed suitable for the study of doping effects. Moreover, the morphological characteristics of both the pristine and doped NiO powders were investigated using a field emission scanning electron microscope coupled with energy dispersive spectroscopy to confirm the presence of dopant elements and chemical composition. The morphological results revealed the growth of homogeneous nanocrystallites with fine particles. Furthermore, the samples underwent Fourier Transform Infrared Spectroscopy analysis to validate their purity, which revealed the presence of vibrational modes in the metal oxide bonds. An optical investigation was conducted on all samples utilizing a diffuse reflectance spectroscopy within the spectral range of 350–900 nm. Band gap values were estimated based on diffuse reflectance spectroscopy data through Tauc plot analysis, yielding a range from 2.77 to 3.46 eV. This analysis revealed a red shift in NiO with all dopants except for Zn doping. Additionally, numerical calculations utilizing the Kramers–Kronig relation were performed to assess the extinction coefficient (k) and refractive index (n) parameters from the reflectance data. The presence of room-temperature ferromagnetism was elucidated in all samples by the findings acquired through the application of the vibrating sample magnetometer technique. The parameters of coercivity exhibit an increase from 80.44 Oe for pristine NiO to 350.75 Oe for Zn-doped NiO, a phenomenon that is advantageous for applications in data storage. The introduction of iron into NiO nanoparticles has profoundly affected the magnetic properties, resulting in a transition of the material from a weak ferromagnetic state to a ferromagnetic state. The outcomes imply promising magnetic and optical applications for such earlier mentioned nanopowders. This observation suggests that the prepared NiO nanopowders have significant potential in both linear and nonlinear optical devices, optoelectronics, and data storage technologies.